2015
DOI: 10.5812/aapm.23923
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Hypnotic Regimens in Patients With Liver Disease; A Review Article

Abstract: Context:The liver as an important organ in the body has many essential functions in physiological processes. One of the major activities of liver is drug metabolism. Hepatic dysfunction affecting hepatic physiological activities, especially drug metabolism can cause many problems during anesthesia and administration of different drugs to patients.Evidence Acquisition:Studies on hepatic disorders and hypnotic anesthetics prescribed in hepatic disorders were included in this review. For this purpose, reliable da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Evidence shows that all NSAIDs have the potential for hepatotoxicity to different degrees (26, 27), which has been suggested as an important reason for withdrawing large numbers of these drugs from the market (e.g., rofecoxib). In most previous research studies and scientific reports, NSAID-induced liver injury has been reported in relation to the chronic use of the drug, while renal injury, gastrointestinal hemorrhage, and respiratory symptoms can occur even in a non-toxic dose (28-31). The mechanism of injury has been cited as hepato-cellular, and it is based on autoimmune issues, mitochondrial injury, and metabolic errors (32).…”
Section: Contextmentioning
confidence: 99%
“…Evidence shows that all NSAIDs have the potential for hepatotoxicity to different degrees (26, 27), which has been suggested as an important reason for withdrawing large numbers of these drugs from the market (e.g., rofecoxib). In most previous research studies and scientific reports, NSAID-induced liver injury has been reported in relation to the chronic use of the drug, while renal injury, gastrointestinal hemorrhage, and respiratory symptoms can occur even in a non-toxic dose (28-31). The mechanism of injury has been cited as hepato-cellular, and it is based on autoimmune issues, mitochondrial injury, and metabolic errors (32).…”
Section: Contextmentioning
confidence: 99%
“…Etomidate as a water and fat soluble carboxylate imidazole is a popular hypnotic agent. It is frequently used for hemodynamically unstable patients ( 3 , 4 , 7 ). In spite of its several benefits, myoclonus as nonepileptic involuntary jerky movements of muscles still remains as a notable side effect ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is associated with some disturbing side effects, such as pain on injection, postoperative nausea and vomiting, adrenal suppression, superficial thrombophlebitis and myoclonus ( 3 , 4 , 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Care should be taken with benzodiazepines and paralytics, due to a reduction in both CYP-3A4 metabolism and PBP resulting in prolonged duration [1,[140][141][142]144,147,150,151], whereas atracurium, lorazepam, oxazepam, and temazepam undergo non-hepatic conjugation [140,152]. Opioids in LC have significantly reduced metabolism [141,147,153] and prolonged half-lives, potentially exaggerating sedative and respiratory depressant effects, in contrast to fentanyl [1,141,147]. Tricyclic antidepressants, pregabalin, and gabapentin do not require hepatic metabolism and are successful in neuropathic pain management [141].…”
Section: Anesthesia Considerationsmentioning
confidence: 99%
“…Although the uptake and onset of anesthetic drug action is unaffected, hepatic clearance is dependent upon volume of distribution, functional hepatic blood flow (HBF), hepatic extraction ratio, hepatic microsomal and cytochrome-P450 enzyme activity, decreased plasma-binding proteins (PBP), and decreased biliary excretion (Table 3) [63, [140][141][142][143][144][145][146][147]. In general, short to intermediate halflive drugs at lower doses with longer dose intervals should be used [140,141].…”
Section: Anesthesia Considerationsmentioning
confidence: 99%